Ethnobotanical Survey of Aromatic and Medicinal Plants Used in Traditional Medicine and Agri-Food in The Fez-Meknes Region - Hamza El Finou; Nadia Salhi; Asma Halmoune; Lhoussaine El Rhaffari (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2023)
In order to identify the medicinal plants used in agri-food and traditional medicine by the population of Fez-Meknes region (Morocco), a floristic and ethnobotanical study was carried out in 4 provinces of this region (Fez, Meknes, Azrou, Taza). Questionnaire forms were used to survey the usual users of the plants and herbalists and to collect as much information as possible on the therapeutic and dietary use of aromatic and medicinal plants in the region. For plants used for food, our survey identified 29 species divided into 26 genera and 16 families, including herbaceous plants (70%), trees (16.60%), shrubs (10%) and bushes (3.30%). The study of the medicinal flora used in traditional medicine also allowed the inventory 81 species belonging to 47 families. Leaves are the most commonly used part and the majority of remedies were prepared in the form of infusion (47%) and decoction (26%). Among all the diseases treated, digestive diseases are the most cited (25%), followed by dermatological diseases (21%). The present study allowed us to evaluate some traditional practices used by the Fez-Meknes region population. In this context, it is essential to carry out similar investigations in other regions of the kingdom, in order to safeguard this precious natural heritage by means of a monograph that is as complete as possible and to validate the remedies and preparations identified using rigorous scientific protocols.